Histopathological and immunological characteristics of placentas infected with chikungunya virus - Salomão, Natália; Rabelo, Kíssila; Avvad-Portari, Elyzabeth; Basílio-de-Oliveira, Carlos; Basílio-de-Oliveira, Rodrigo; Ferreira, Fátima; Ferreira, Luiz; de Souza, Thiara Manuele; Nunes, Priscila; Lima, Monique; Sales, Anna Paula; Fernandes, Regina; et al. (Frontiers in Microbiology, 2022)
Although vertical transmission of CHIKV has been reported, little is known about the role of placenta in the transmission of this virus and the effects of infection on the maternal-fetal interface. In this work we investigated five placentas from pregnant women who became infected during the gestational period. Four formalin-fixed paraffin-embedded (FFPE) samples of placenta (cases 1-4) were positive for CHIKV by RT-PCR. One (case 5) had no positive test of placenta, but had positive RT-PCR for CHIKV in the serum of the mother and the baby, confirming vertical transmission. The placentas were analyzed regarding histopathological and immunological aspects. The main histopathological changes were: deciduitis, villous edema, deposits, villous necrosis, dystrophic calcification, thrombosis and stem vessel obliteration. In infected placentas we noted increase of cells (CD8+ and CD163+) and pro- (IFN-γ and TNF-α) and anti-inflammatory (TGF-β and IL-10) cytokines compared to control placentas. Moreover, CHIKV antigen was detected in decidual cell, trophoblastic cells, stroma villi, Hofbauer cell and endothelial cell. In conclusion, CHIKV infection seems to disrupt placental homeostasis leading to histopathological alterations in addition to increase in cellularity and cytokines overproduction, evidencing an altered and harmful environment to the pregnant woman and fetus.